PENGARUH WAKTU, LEVEL PROTEIN PAKAN DAN PAPARAN LASERPUNKTUR TERHADAP PENINGKATAN NILAI Gonado Somatic Index (GSI) INDUK IKAN LELE (Clarias sp) - Pungky Slamet Wisnu Kusuma; Dyah Hariani (FMIPA : Universitas PGRI Adi Buana, 2016)
Laserpuncture exposure at the reproductive acupoint of broodstock catfishes female shown to speed maturation of the gonads. To accelerate the gonadal maturation broodstock catfish due to exposure needed laserpuncture adequate feed, especially protein content results. if laserpuncture exposure is not balanced feeding containing adequate protein, the lower quality of eggs produced. The purpose of this study to examine whether time, the level of protein in the feed and laserpuncture exposure broodstock catfish female can increase the value of GSI. RAK experimental study using a 3x5x2 factorial pattern was repeated 3 times. Factor 1 is the feed protein level of 30%, 35%, and 40%. Factor 2 is pre-spawning time, weeks 0, 3rd, 6th and 9th. Factor 3 is laserpuncture exposure and control. To get the value of GSI by weighing the weight and gonads. The sample used in this study broodstock catfish 1-year-old female with a weight range from 1100 to 1400 grams have never spawned. GSI value analysis using ANOVA Gen Stat program version 15. Results showed laserpuncture exposure at the reproduction acupoint of which is offset by the provision of feed protein level of 30%, 35% and 40% and the length of time proved to have a significant effect (P <0.05) increase in value GSI. The length of time, giving the feed protein level of 30% and laserpuncture exposure proved effective to increase the value of GSI, gonad maturation time can be accelerated three weeks compared to the control group. Keywords: Time, Level Protein Feed, catfish Betina, Laserpuncture and the value of GSI